Kidneys in Hypertensive Rats Show Reduced Response to Nitric Oxide Synthase Inhibition as Evaluated by BOLD MRI - Li, Luping (2003)
PURPOSE: To examine whether the noninvasive technique of blood oxygenation level dependent magnetic resonance imaging (BOLD MRI) can detect changes in renal medullary oxygenation following administration of a nitric oxide (NO) synthase inhibitor, N(G)-nitro-L-arginine methyl ester (L-NAME). Hypertension is associated with endothelial dysfunction and is characterized by a lack of response to endothelial-dependent vasoactive substances, including nitric oxide synthase inhibitors. We hypothesized that the magnitude of the change would be reduced in the kidneys of hypertensive subjects relative to normal controls. MATERIALS AND METHODS: To test this hypothesis, data were obtained in spontaneously hypertensive rats (SHR, n = 6). Wistar-Kyoto rats (WKY, n = 7) were used as normotensive controls. RESULTS: As expected, WKY rats showed a significant response to L-NAME (R(2)* increasing from 23.6±1.5 Hz to 32.5±2.2 Hz, P < 0.05), while SHR exhibited a minimal change in medullary oxygenation (R(2)* measuring 31.9±2.8 Hz pre- and 35.5±2.2 Hz post-L-NAME). The baseline R(2)* in SHR is found to be comparable to post-L-NAME values in WKY rats, suggesting a basal deficiency of nitric oxide in SHR. CONCLUSION: Based on the differential effect of NO synthase inhibition on medullary oxygenation, BOLD MRI can distinguish hypertensive from normal kidney. Our results are consistent with previously reported observations using invasive methods.